Hector and The Search For Happiness - LELORD, Francois (Penguin Books (USA), 2010)
Once Upon a Time there was a young psychiatrist called Hector who was not very satisfied with himself ..And so he decided to take a trip around the world, and everywhere he went he would try to understand what made people happy or unhappy.